2019
DOI: 10.1017/s0007114519001181
|View full text |Cite|
|
Sign up to set email alerts
|

Programme National Nutrition Santé – guidelines score 2 (PNNS-GS2): development and validation of a diet quality score reflecting the 2017 French dietary guidelines

Abstract: Following the revision of the French dietary guidelines in 2017, the Programme National Nutrition Santé – guidelines score (PNNS-GS), built upon previous recommendations released in 2001, needed to be updated. This cross-sectional study thus aimed to develop and validate the PNNS-GS2, a predefined food-based dietary index based on the 2017-revised French nutritional guidelines. A total of 80 965 participants recruited among French adults (≥18 years old) in the NutriNet-Santé web-based prospective cohort were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 37 publications
8
78
0
Order By: Relevance
“…Adherence to the French dietary recommendations was evaluated during the month before the lockdown and during the first month of the lockdown using the simplified PNNS-GS2 (sPNNS-GS2), an index previously designed to reflect the 2017 French main dietary recommendations ( Chaltiel et al, 2019 ). The sPNNS-GS2 builds on the distinction between malus components (less healthy food groups which consumption should be limited, carrying a negative score, i.e., red meat, processed meat, sugary foods, sweet-tasting beverages, alcoholic beverages, salt) and bonus components (healthier food groups carrying a positive score, i.e., fruits and vegetables, nuts, legumes, whole-grain food, milk and dairy products, fish and seafood).…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to the French dietary recommendations was evaluated during the month before the lockdown and during the first month of the lockdown using the simplified PNNS-GS2 (sPNNS-GS2), an index previously designed to reflect the 2017 French main dietary recommendations ( Chaltiel et al, 2019 ). The sPNNS-GS2 builds on the distinction between malus components (less healthy food groups which consumption should be limited, carrying a negative score, i.e., red meat, processed meat, sugary foods, sweet-tasting beverages, alcoholic beverages, salt) and bonus components (healthier food groups carrying a positive score, i.e., fruits and vegetables, nuts, legumes, whole-grain food, milk and dairy products, fish and seafood).…”
Section: Methodsmentioning
confidence: 99%
“…The PNNS-GS2 is a score that reflects adherence to the 2017 French nutritional guidelines ( Table 1 ) [ 28 ]. Briefly, it includes 13 components, of which seven are considered as adequacy recommendations and six refer to moderation recommendations.…”
Section: Diet Quality and Metabolic Syndromementioning
confidence: 99%
“…Similar to the aHEI, the PNNS-GS2 has no specific sub-score for SFA, but SFA intake is captured by the recommendation on added fat (to favor vegetable sources of fat vs. animal sources of fat) and indirectly by the recommendation on processed meats. Hence, individuals with a higher PNNS-GS2 consumed less SFA than individuals with a lower score [ 28 ]. Cross-sectional data from the Nutrinet-Santé Study have shown that a higher PNNS-GS2 was associated with a lower BMI, lower TG and glucose concentrations, lower systolic and diastolic blood pressures, and with higher concentrations of HDL-C in both men and women [ 28 ].…”
Section: Diet Quality and Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, milk proteins (whey and casein) are nutritionally complete and highly digestible, with high amino acid scores, and contain all amino acids in amounts sufficient to support the maintenance of all body proteins [ 29 , 30 ]. Due to its nutrient profile, the dietary guidelines of most Western countries recommend at least 2–3 daily servings of milk or milk products [ 15 , 31 , 32 , 33 ]. The Korean Nutrition Society recommends that Korean adults consume at least one serving of milk per day [ 34 ].…”
Section: Introductionmentioning
confidence: 99%